Complex treatment of recurrent pulmonary vein stenosis - Mykychak, Y. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Pulmonary vein stenosis (PVS) in children is a rare heart disease characterized by high recurrence and mortality rates. Objective. We describe a case of recurrent PVS, which was treated surgically and subsequently with repeated balloon angioplasties. Materials and methods. Echocardiogram showed total anomalous pulmonary venous connection, mixed form. A CT scan of the chest confirmed the diagnosis. Month later after initial surgery angiography detected the presence of stenosis in all pulmonary veins. Results. Currently patient has moderate residual stenosis in each PV. His prognosis is considered bleak due to continuous requirement in aggressive interventions in order at least temporarily resolve pulmonary vein stenosis. Conclusions. Pulmonary vein stenosis still bears high recurrence, reintervention and mortality rates. Rigorous surveillance and combination of surgical and interventional treatment is warranted in this subset of patients to maintain quality of life.